2003
DOI: 10.1038/sj.jhh.1001561
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and vascular remodelling, in relation to left ventricular mass, geometry and function: an answer to LIFE?

Abstract: Many pathophysiological processes have been intimately linked to hypertension and its complications, including insulin resistance, left ventricular mass (LVM) and geometry, central vascular hypertrophy and peripheral vascular remodelling, LV systolic and diastolic function, etc. What appears to be much less certain are the (complex) interrelations between all these diverse processes.In elderly patients with essential hypertension and LV hypertrophy (LVH), Olsen et al 1 recently reported that peripheral vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…It is important to note that adjustment for indices of adiposity appeared to account for most of the reduction in the magnitude of diabetes associations seen in multiply-adjusted models. This finding was suggested by Galvan et al[28], and is consistent with a recent review that concluded that associations of insulin and glucose metabolism with LV mass were mostly explained by adiposity [29]. In fact, one of the largest studies to date, the HyperGEN Study, with adequate representation of African-Americans, found inverse associations with fasting insulin levels and adaptive LV responses, once adjustment for several elements of the insulin resistance syndrome was performed [30].…”
Section: Discussionsupporting
confidence: 92%
“…It is important to note that adjustment for indices of adiposity appeared to account for most of the reduction in the magnitude of diabetes associations seen in multiply-adjusted models. This finding was suggested by Galvan et al[28], and is consistent with a recent review that concluded that associations of insulin and glucose metabolism with LV mass were mostly explained by adiposity [29]. In fact, one of the largest studies to date, the HyperGEN Study, with adequate representation of African-Americans, found inverse associations with fasting insulin levels and adaptive LV responses, once adjustment for several elements of the insulin resistance syndrome was performed [30].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with the cardiovascular remodeling observed in insulin-resistant diabetic subjects (20). However, most diabetic patients exhibiting cardiac remodeling are hypertensive, a common comorbidity of diabetes that may contribute to diabetic heart disease (38).…”
Section: Insulin Resistance In Ins2supporting
confidence: 81%
“…Consequently, an increase in LVMI and disturbance in diastolic functions may be expected [1]. However, the common belief is that the influential mechanisms are not limited to hemodynamic changes [9]. The negative relation between adiponectin and LVMI may also contribute to this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Although changes to the heart caused by obesity are wellknown, the effective mechanisms are not. Despite largely emphasized hemodynamic effects, other metabolic and inflammatory factors may also exist [9].…”
Section: Discussionmentioning
confidence: 99%